Penguatan Nilai-Nilai Moderasi Beragama Dan Multikulturisme Pada Universitas Muslim Indonesia (UMI) Makassar - Wahyuddin, Wahyuddin (Jurnal Ilmiah Islamic Resources, 2021)
Multiculturalism is the best expression that represents the face of Indonesia which describes the reality of this country by mentioning it as a country that has incomparable diversity on this earth. That the diversity of Indonesian society is destiny, it is a gift from God that is not to be bargained for but to be taken for granted. This diversity is a great potential in building and advancing the nation and state, but on the other hand, if this diversity potential is not managed properly it will become the seed of division and potential conflict in the community that can damage the unity and integrity of the nation. In fact, the diversity of religions and cultures gives birth to peace and shade for adherents and citizens. But in reality, religious and cultural differentiation sometimes triggers the emergence of tension and disharmony in society with various accompanying cases, so the values of moderation and multiculturalism are absolutely necessary as an alternative and solution to the attitude of diversity in society which tends to be radical and anarchic. The more complex and diverse the pattern of people's lives, including the pattern of community diversity with the presence of transnational religious and national understandings that can damage the integrity of the Indonesian nation, the role of educational institutions including higher education is very strategic in instilling and providing strengthening values of religious moderation and strengthening multicultural understanding. And that role is recognized and has received attention at the Muslim University of Indonesian Makassar, especially in teaching materials for religious subjects and in the Pencerahan Qalbu program